2007
DOI: 10.1016/j.jaap.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray diffraction investigation of thermal decomposition of wood cellulose

Abstract: The kinetics of thermal decomposition of crystalline cellulose in spruce wood (Picea abies [L.] Karst.) was studied by in-situ X-ray diffraction using synchrotron radiation. Fiber diffraction patterns resulting from the crystal lattice of native cellulose arranged in oriented microfibrils were collected as a function of heat treatment time for various temperatures from 300 to 360°C. Sample heating was performed using a specially designed in-situ pyrolysis A c c e p t e d M a n u s c r i p t 2 meridional diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…The lignin rich CML remained optically nearly unchanged (Figure 3b). c) From 2508C to 2758C: the crystallite size declines (Zickler et al 2007) and this is accompanied by an iso-orientation of the cellulose microfibrils (loosing their preferred orientation with a specific MFA) and the CML is also decomposed ( Figure 3c). d) 3008C: amorphisation of the cell wall proceeds to a disintegrated and fully random structure (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lignin rich CML remained optically nearly unchanged (Figure 3b). c) From 2508C to 2758C: the crystallite size declines (Zickler et al 2007) and this is accompanied by an iso-orientation of the cellulose microfibrils (loosing their preferred orientation with a specific MFA) and the CML is also decomposed ( Figure 3c). d) 3008C: amorphisation of the cell wall proceeds to a disintegrated and fully random structure (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2001) proposed first models on the thermally induced decomposition of cellulose microfibrils in wood including reduction of crystallinity (cellulose decomposition) along the fibre axis and rapid decomposition of individual microfibrils, while others are still intact. Recently, Zickler et al (2007) anticipated another model involving degradation starting from the equatorial surfaces of the cellulose crystallites, where initial decomposition should occur at the boundaries between the cellulose microfibrils and the polyoses. However, EM studies on wood treated at mild temperatures are scarce in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zickler et al (2007) also reported that the thermal decomposition of cellulose is mainly via a thermally activated decrease of the cellulose diameter. …”
Section: Pyrolysis Of Pretreated MCCmentioning
confidence: 97%
“…Currently aerospace, automotive and construction applications employ Polymer-Fibre Composites systems with loading levels ranging from 15 to 65% weight of fibre reinforcements. This approach improves most mechanical properties [1][2][3][4][5] Biomass in fibre or particulate form has been used as reinforcing filler in polymeric composites materials. However, they present limitations such as moisture adsorption and low thermal stability [6,3].…”
Section: Introductionmentioning
confidence: 99%